KAJIAN PENANGGULANGAN BAHAYA KEBAKARAN PADA PERUMAHAN (SUATU KAJIAN PENDAHULUAN DI PERUMAHAN SARIJADI BANDUNG) - Wirawibawa Mantra, Ida Bagus Gede (Jurnal Natah, 2012)
The highest number of Indonesia’s fire incidents occurs in housing areas. Besides high fire loads, it is also caused by high building density areas. In generally, it is can be easily for hundreds of people losing their homes and lives. This is a preliminary study of housing’s condition which related to fire hazard. It will not make a model of measure planning, but conduct conceptual approach only. It is compare any literature with condition of Sarijadi Bandung housing as a case study. The result shows that condition of Sarijadi housing is lack of fulfill fire requirement, especially lack of fire prevention equipment, lack of water for fire fighting, difficulty in accessing the fire location, building’s compartment and other. So I suggest that fire safety in Sarijadi housing must conduct inter houses compartment with fire retardant material; access and water for fire fighting; and areas for vehicle’s turning radius.
Keywords: building density, fire load, and compartment.